(untitled) (Clinics, 2022)
Objectives: Defense against respiratory viruses depends on an immune response present in the mucosa, as saliva IgA secretes antibodies. During the pandemic, such as influenza or SARS-CoV-2, most infected patients are asymptomatic but retain specific antibodies post-infection. The authors evaluated IgG and IgA antibodies against SARS-CoV-2 and influenza in the saliva of asymptomatic volunteers, validated with controls or vaccinated individuals. Methods: The authors detected specific antibodies by validated conventional ELISA using natural SARS-CoV-2 antigens from infected Vero cells or capture-ELISA for influenza using natural antigens of the influenza vaccine. Results: Saliva from influenza-vaccinated individuals had more IgA than paired serum, contrary to the findings for specific IgG. In COVID-19-vaccinated samples, specific IgA in saliva increased after vaccination, but IgG levels were high after the first dose. In saliva from the asymptomatic population (226), anti-Influenza IgG was found in 57.5% (130) of samples, higher than IgA, found in 35% (79) of samples. IgA results were similar for SARS-CoV-2, with IgA present in 30% (68) of samples, while IgG was less present, in 44.2% (100) of samples. The proportion of influenza IgG responders was higher than that for SARS-CoV-2 IgG, but both populations presented similar proportions of IgA responders, possibly due to variable memory B cell survival. For both viruses, the authors found an important proportion (> 10%) of IgA+IgG- samples, suggesting the occurrence of humoral immunity directed to the mucosa. Conclusion: Specific antibodies for respiratory viruses in saliva are found in either infection or vaccination and are a convenient and sensitive diagnostic tool for host immune response.